Exploring the influence of romantic relationships on young adolescent men's sexual and reproductive health attitudes and practices - Tolla, Tsidiso (Department of Public Health and Family Medicine, 2025)
Romantic relationships serve as a training ground for the development and improvement of interpersonal negotiation and communication skills where adolescents may learn how to cater to their emotional and sexual needs and those of their partners. Sexual activity is common in adolescent romantic relationships, where adolescents may learn how to negotiate consent, communicate their sexual needs, and learn about their sexual preferences. While sex is not necessarily risky, it exposes adolescents to HIV, sexually transmitted infections (STIs), and pregnancy. In heterosexual romantic relationships, which are a focus of this study, gendered power dynamics become a crucial component with serious implications for sexual decision-making and sexual negotiation, including HIV and intimate partner violence (IPV). This qualitative study explored young adolescent men's experiences of heterosexual romantic relationships and how these shape their sexual and reproductive health (SRH), HIV, and IPV-related attitudes and practices. Specifically, the study explored (a) sexual negotiation and decision making (b) gendered power dynamics, and (c) young adolescent men's experiences and perceptions of IPV. Twenty-eight young adolescent men aged 14 to 19 years old from Gugulethu, Cape Town took part in individual interviews conducted telephonically and through WhatsApp. Thirteen young adolescent men participated in handwritten diary entries and a total of 8 in-person FGDs, with a minimum of four young adolescent men per group, were conducted. All data were transcribed, translated, and coded using NVivo software. Thematic and discourse analysis were used to analyse the data. Findings highlight that in heterosexual romantic relationships, young adolescent men oscillated between challenging and reinforcing gender norms, with mixed feelings of uncertainty, fear, and self-doubt. They also grappled with their desires for intimacy and emotional connection with their 2 partners, while negotiating their masculinities. The findings suggest that young adolescent men's sexual practices, their perceptions of risk to HIV, and STIs, and their attitudes towards IPV are located in and influenced by the romantic relationship context. As such, efforts towards improving the SRH of adolescents will require specific attention to romantic relationship dynamics.